Pemanfaatan Limbah Kulit Singkong Sebagai Bahan Tambah Semen Pada Campuran Beton - Eleazar P. P. Pakilaran; Luciana Buarlele; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2025)
This study uses cassava peel ash as a cement additive in concrete mixtures. As an important crop in many tropical countries, cassava produces a lot of waste during its processing, mostly in the form of cassava peels. One interesting material is cassava peel ash from cassava processing which is added to concrete. The purpose of this study was to determine the effect of cassava peel ash (AKS) addition in varying amounts to cement, namely 0%, 2%, 4%, and 6% on the compressive strength, split tensile strength, and flexural strength values of concrete mixtures. The mix design method uses SNI 7565:2012, fresh concrete testing uses SNI 1973:2008, compressive strength SNI 1974:2011, split tensile strength SNI 2491:2014, and flexural strength of concrete using SNI 4431:201. This research was conducted in the Concrete Laboratory of Civil Engineering of Universitas Kristen Indonesia Paulus. Based on the weight of cement, the amount of cassava peel ash used varied from 0%, 2%, 4%, and 6%. The compressive strength that meets the plan quality is found in variations of 0, and 2%, for split tensile strength and flexural strength, the variation in the addition of AKS values decreases. Concrete quality decreased with increasing AKS variation.